Comparison of Martian surface ionizing radiation measurements from MSL‐RAD with Badhwar‐O'Neill 2011/HZETRN model calculations. Issue 6 (17th June 2014) - Kim, Myung‐Hee Y.; Cucinotta, Francis A.; Nounu, Hatem N.; Zeitlin, Cary; Hassler, Donald M.; Rafkin, Scot C. R.; Wimmer‐Schweingruber, Robert F.; Ehresmann, Bent; Brinza, David E.; Böttcher, Stephan; Böhm, Eckart; Burmeister, Soenke; et al.
Abstract: Dose rate measurements from Mars Science Laboratory‐radiation assessment detector (MSL‐RAD) for 300 sols on Mars are compared to simulation results using the Badhwar‐O'Neill 2011 galactic cosmic ray (GCR) environment model and the high‐charge and energy transport (HZETRN) code. For the nuclear interactions of primary GCR through Mars atmosphere and Curiosity rover, the quantum multiple scattering theory of nuclear fragmentation is used. Daily atmospheric pressure is measured at Gale Crater by the MSL Rover Environmental Monitoring Station. Particles impinging on top of the Martian atmosphere reach RAD after traversing varying depths of atmosphere that depend on the slant angles, and the model accounts for shielding of the RAD "E" detector (used for dosimetry) by the rest of the instrument. Simulation of average dose rate is in good agreement with RAD measurements for the first 200 sols and reproduces the observed variation of surface dose rate with changing heliospheric conditions and atmospheric pressure. Model results agree less well between sols 200 and 300 due to subtleties in the changing heliospheric conditions. It also suggests that the average contributions of albedo particles (charge number Z  < 3) from Martian regolith comprise about 10% and 42% of the average daily point dose and dose equivalent, respectively. Neutron contributions to tissue‐averaged effective doses will be reduced compared to point dose equivalent estimates because a large portion of the neutron point dose is due to low‐energy neutrons with energies <1 MeV, which do not penetrate efficiently to deep‐seated tissues. However the exposures from neutrons to humans on Mars should become an important consideration in radiobiology research and risk assessment. Key Points: Model simulation agrees with RAD measurements on Mars surface Dose rate varies with heliospheric condition and atmospheric pressure Neutron flux on Mars to be considered for radiobiology and risk assessments